2005
DOI: 10.1159/000088438
|View full text |Cite
|
Sign up to set email alerts
|

Production of Salivary Immunoglobulin A and Suppression of <i>Dermatophagoides pteronyssinus</i>-Induced Airway Inflammation by Local Nasal Immunotherapy

Abstract: Background: Local nasal immunotherapy (LNIT) is an effective immunotherapeutic modality, especially when targeting a single immunodominant peptide from an allergen. However, the working mechanisms of LNIT are poorly understood. We hypothesized that LNIT with a mixture of group 2 allergens of Dermatophagoides pteronyssinus (Der p 2) protein and fungal immunomodulatory peptide (FIP) would generate suppression of Der p-induced airway inflammation through immunoglobulin (Ig) A secretion in the airways. Method: Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…4,16 According to our previous animal model and other reports, IgE was elevated in mice sera before allergen sensitization and was decreased after treatment. 8,17 Similar findings were observed after LNIT with DNDp. Significantly, decreased Der p-specific IgE may be due to decreased production of IL-4 in Th2 cells.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…4,16 According to our previous animal model and other reports, IgE was elevated in mice sera before allergen sensitization and was decreased after treatment. 8,17 Similar findings were observed after LNIT with DNDp. Significantly, decreased Der p-specific IgE may be due to decreased production of IL-4 in Th2 cells.…”
Section: Discussionsupporting
confidence: 74%
“…8 Briefly, aerosol was generated by placing 200 ul of saline or different doses of methacholine (0, 12.5, 25, and 50 mg/ml; Sigma) solution in the cup of an ultrasonic nebulizer. It was delivered via a connecting tube and a 3-way connector to the animal chamber of the plethysmograph.…”
Section: Pulmonary Function Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Treg cells were observed from stimulating PBMCs of Dermatophagoides farinaesensitized allergic rhinitis patients with a peptide containing the N-terminal 63 residues of Der f 2 in combination with Fve ). Furthermore, in a mouse model for local nasal immunotherapy, Der p 2-sensitized mice treated with either Der p 2 peptide or Der p 2 plus Fve could downregulate not only Der p 2-specific IgE and Th2 immune responses but also Der p 2-induced airway inflammation and airway hypersensitivity (Liu et al 2003;Liu and Tsai 2005). These results suggested that Fve could execute its immunomodulatory function on the established adaptive immunity by enhancing the number and the function of allergen-specific Treg cells, possibly via its potent activity in stimulating IFN-c production.…”
Section: Discussionmentioning
confidence: 99%
“…Fve was able to induce mitogenic proliferation of human peripheral mononuclear cells (PBMCs) and enhance mRNA transcription of interleukin (IL)-2 and interferon (IFN)-c in vitro (Ko et al 1995;Wang et al 2004). Administration of Fve with allergens either intraperitoneally, orally, or intranasally inhibited allergeninduced systemic anaphylactic responses (Ko et al 1995), food allergic reactions (Hsieh et al 2003), or allergic airway inflammation (Liu et al 2003;Liu and Tsai 2005;Hsieh et al 2007) in vivo, respectively. Recently, Fve has also been shown to exhibit potent adjuvant properties that enhanced the immunogenicity of the human papillomavirus type-16 (HPV-16) E7 oncoprotein and conferred increased antitumor effects against the inoculation of HPV-16 E7-expressing TC-1 cells in a mouse model (Ding et al 2009).…”
Section: Introductionmentioning
confidence: 99%